Optical Solitons with Differential Group Delay and Inter-Modal Dispersion Singlet (Contemporary Mathematics, 2024)
This paper introduces a state of the art investigation into the interaction between soliton propagation and differential group delay, offering a fresh perspective often neglected in previous studies. Motivated by the imperative to comprehend soliton behavior within inter-modal dispersion environments, it presents three innovative methodologies aimed at uncovering novel optical soliton solutions. Through the utilization of cutting-edge algorithms, these approaches unveil the emergence of solitons in hitherto unexplored contexts. The research makes significant strides through extensive numerical simulations, which not only validate theoretical conjectures but also offer practical insights. Furthermore, it delineates crucial parameter limitations essential for the existence of solitons, thus furnishing valuable guidance for future research endeavors and practical applications.
Keywords: traveling waves, csch-function method, extended simplest equation method, tanh-coth approach